Structure Analysis of Sulfated Polysaccharides Extracted from Scinaia interrupta: A Experimental and Density Functional Theory Studies - Acharjee, Nivedita; Ghosh, Tuhin (Asian Journal of Chemistry, 2020)
In present report, a combined experimental and theoretical study has been performed to address the isolation procedure and spectroscopic structure elucidation of polysaccharides such as xylomannan isolated from marine red algal source Scinaia interrupta. The structure of the polysaccharides obtained from the red algae of Scinaia interrupta has been studied from NMR, IR and GC-MS spectroscopy. The investigation revealed that red algae contained a backbone of α-(1→4)-linked D-mannopyranosyl residues substituted at 6-position with a single stub of β-D-xylopyranosyl residues. The major polysaccharide, which had 0.6 sulfate groups per monomer unit and an apparent molecular mass of 120 KDa. The backbone structure was optimized at DFT/B3LYP/6-311G(d,p) level of theory and GIAO-NMR studies were performed at B3LYP/6-311++G(2d,p) level of theory followed by mean absolute error calculations of the computed chemical shifts for two possible conformers resulting from the flipping of xylopyranosyl residue. The NMR calculations were in agreement with the experimental findings. The experimental 1H NMR chemical shifts were then correlated with the NBO, Merz Kollman (MK), ChelpG and Mulliken charges of the predicted conformer. A reasonable correlation with the experimental 1H NMR chemical shifts and the computed NBO charges with correlation coefficient of 0.906.